East Timor Beyond the Ballot - Horta, James Ramos (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Before Indonesia elected a new president and Indonesian troops made their long-overdue exodus from East Timor to give way to the former Portugese colony's statehood, Dr. Jose Ramos Horta anticipated his people choosing independence over autonomy. During his visit at the Asian Center, University of the Philippines-Diliman, on July 28, 1999, Dr. Horta shared his hopes for a tiny nation-to-be and saw a promising future for his people if only given the chance to live in peace.
Keywords: East Timor, Dr. Jose Ramos Horta, University of the Philippines-Diliman